« QUAND UNE FEMME ÉBRIÉ ACCOUCHE, ON LA TRAITE AVEC LES MÊMES SOINS JUSQU’AUJOURD’HUI, POUR QU’ELLE GROSSISSE ! » : ETUDE DE LA DIMENSION IDENTITAIRE DU « TAMBRUYA » À ABIDJAN - Adiko A Francis; Yao Y Léopold; Amani N Georges (European Scientific Journal, ESJ, 2012)
In Abidjan, the prevalence of metabolic syndrome is higher among women and people of Akan ethnic group. As is the case among people of Akan Lagoon, the appreciation of feminine curves explains the submission of nursing mothers of Ebrie ethnic in « Tambruya ». Despite the risk of overeating and oversleeping due to the appreciation of overweight, the role of this tradition has been neglected until now in the etiology of metabolic diseases. Semi-structured interviews with 10 nurses have brought about the meaning of « Tambruya » instead of overweight in relation to the canons of female beauty of Ebrie and perceptions of risk of these diseases. The research has demonstrated the legitimacy of « Tambruya » as a therapy and an expression means of ethnic identity Ebrie. Its has also shown the perception of the introduction of vitamin products in food and sorcery as causes of metabolic diseases.